Genetic differentiation among selected tepary bean collections revealed by morphological traits and simple sequence repeat markers. (3rd October 2018) - Mhlaba, Zinhle Babongile; Amelework, Beyene; Shimelis, Hussein; Modi, Albert Thembinkosi; Mashilo, Jacob
ABSTRACT: Understanding the genetic relationship of crop ideotypes is essential for genetic analysis and breeding. The objective of this study was to determine genetic differentiation present among 20 selected tepary bean ( Phaseolus acutifolius A. Gray) genotypes using morphological traits and simple sequence repeat (SSR) markers in order to identify genetically unique parental lines to develop breeding populations. Phenotypic diversity was estimated using Shannon-Weaver diversity index (H'), principal component analysis (PCA) and cluster analysis (CA). Genotypic diversity was estimated using Jaccard's genetic distances and CA. Shannon-Weaver diversity index values for the studied morphological traits ranged from 0.89 to 0.99, with a mean of 0.95 revealing high phenotypic differences among test genotypes. PCA identified four useful principal components (PC's) which contributed to 73% of the total phenotypic variation of collections. PC1 accounted for 28% of the total variation correlated to dry shoot mass and number of pods per plant. PC2 correlated with number of seeds per pod, grain yield and harvest index and contributed to 21% of total variation. The mean observed ( H o ) and expected ( H e ) heterozygosity values were 0.45 and 0.51, respectively revealing moderate genetic differentiation among genotypes. The mean polymorphic information content was 0.52, suggesting efficient discriminatory power of the SSR loci useful in future tepary bean genetic diversity analysis. The current study revealed moderate genetic differentiation among the studied tepary bean genotypes. Morphological traits and SSR markers well-correlated in allocating the tepary bean genotypes. The following genotypes were genetically distinct: G40201, G40237, G40068, G40033 and G40063 which are recommended for further crosses, selection and population development.